ZDHHC11 Positively Regulates NF-κB Activation by Enhancing TRAF6 Oligomerization - Liu, Enping; Sun, Jiawei; Yang, Jing; Li, Lin; Yang, Qili; Zeng, Jiuqin; Zhang, Jiayu; Chen, Dahua; Sun, Qinmiao (Frontiers in Cell and Developmental Biology, 2021)
Tumor necrosis factor receptor-associated factor 6 (TRAF6) is a RING domain ubiquitin ligase that plays an important role in nuclear factor-κB (NF-κB) signaling by regulating activation of the TAK1 and IKK complexes. However, the molecular mechanisms that regulate TARF6 E3 activity remain unclear. Here, we found that ZDHHC11, a member of the DHHC palmitoyl transferase family, functions as a positive modulator in NF-κB signaling. ZDHHC11 overexpression activated NF-κB, whereas ZDHHC11 deficiency impaired NF-κB activity stimulated by IL-1β, LPS, and DNA virus infection. Furthermore, Zdhhc11 knockout mice had a lower level of serum IL6 upon treatment with LPS and D-galactosamine or HSV-1 infection than control mice. Mechanistically, ZDHHC11 interacted with TRAF6 and then enhanced TRAF6 oligomerization, which increased E3 activity of TRAF6 for synthesis of K63-linked ubiquitination chains. Collectively, our study indicates that ZDHHC11 positively regulates NF-κB signaling by promoting TRAF6 oligomerization and ligase activity, subsequently activating TAK1 and IKK complexes.